Comparative of Media Factors from Sawdust Sengon, Jabon and Spent Oyster Mushroom Substrate Mixture on the Mycelial Growth of Oyster Mushroom (Pleurotus spp.) - Abdurachman Syafiih; Achmad .; Elis Nina Herliyana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Oyster mushroom (Pleurotus spp.) is a potential fungus that is regularly consumed by general public. This research aims to get qualified spawn of Pleurotus spp. by testing the growth of colony diameter and mycelial biomass on two mediums; PDA and MEYEA, as well as the addition of sawdust. The research was carried out using Pleurotus spp. isolates on different mediums and sawdust mixture. The results indicated that both Pleurotus spp. isolates grew better on MEYEA compared to PDA. Isolates of P. ostreatus TP and P. ostreatus var. columbinus TB both have an average growth speed of 0.90 cm/day and mycelial biomass of 0,19 g. Both Pleurotus spp. isolates grown on MEYEA medium that had previously been mixed with spent oyster mushroom substrate and Jabon (Anthocephalus cadamba) sawdust grew better than the other medium mixed with Sengon (Falcataria moluccana) - both have an average growth speed of 1,06 cm/day and mycelial biomass of 0,26 g; while both isolates on medium mixed with Sengon sawdust have an average growth speed of 0,34 cm/day and mycelial biomass of 0,23 g.Keywords: biomass, diameter growth, Pleurotus spp, sawdust Sengon, sawdust Jabon, spent oyster mushroom substrate,